Study of Right Ventricular Involvement in Acute Inferior Myocardial Infarction in Hospitalised Patients - Uddin, M Faruque; Akhtaruzzaman, KM; Kundu, AK; Basak, SK; Dey, SR (Medicine Today, 2012)
Medicine Today 2011 Volume 23 Number 01 Page 22-26 DOI: http://dx.doi.org/10.3329/medtoday.v23i1.11940